2016
DOI: 10.1038/srep36424
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the presence of nucleic acids and β-glucan in the matrix of non-typeable Haemophilus influenzae in vitro biofilms

Abstract: Non-typeable Haemophilus influenzae (NTHi) is a Gram-negative bacterium that frequently colonizes the human nasopharynx; it is a common cause of chronic and recurrent otitis media in children and of exacerbations of chronic obstructive pulmonary disease. To date, no exopolysaccharide clearly contributing to NTHi biofilms has been identified. Consequently, there is some debate as to whether NTHi forms biofilms during colonization and infection. The present work shows that NTHi can form biofilms in vitro, produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 76 publications
0
31
0
Order By: Relevance
“…Biofilm formation was determined with a modified CV assay (26). NT H. influenzae was grown at 37°C under 5% CO 2 in sBHI medium to an optical density at 550 nm (OD 550 ) of 0.5, sedimented by centrifugation, resuspended in an equal volume of s(CϩY) medium (22), and diluted 10-or 100-fold. NE S. pneumoniae P233 was grown at 37°C in CϩY medium to an OD 550 of ϳ0.5, sedimented by centrifugation, resuspended in an equal volume of s(CϩY), and diluted 10-or 100-fold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation was determined with a modified CV assay (26). NT H. influenzae was grown at 37°C under 5% CO 2 in sBHI medium to an optical density at 550 nm (OD 550 ) of 0.5, sedimented by centrifugation, resuspended in an equal volume of s(CϩY) medium (22), and diluted 10-or 100-fold. NE S. pneumoniae P233 was grown at 37°C in CϩY medium to an OD 550 of ϳ0.5, sedimented by centrifugation, resuspended in an equal volume of s(CϩY), and diluted 10-or 100-fold.…”
Section: Methodsmentioning
confidence: 99%
“…NT H. influenzae isolated from patients with AOM, cystic fibrosis (CF), or chronic obstructive pulmonary disease (COPD) has been proposed to form biofilms in vitro and in vivo (19)(20)(21), although a biofilm-specific extracellular polysaccharide has never been described. Indeed, we have recently shown that NT H. influenzae strains are also capable of forming in vitro a true biofilm matrix composed of a ␤-glucan together with proteins and nucleic acids (22).…”
mentioning
confidence: 99%
“…, staining with a variety of DNA-specific fluorophores) to disclose the presence of eDNA in pneumococcal biofilms (79, 11, 26, 27). Immunostaining with α-dsDNA combined with CLSM also revealed the existence of long filaments of eDNA in biofilms formed either by Enterococcus faecalis (45) or Haemophilus influenzae ECM (46). Moreover, the presence of eDNA-containing fibrous structures in the ECM of Staphylococcus aureus and Propionibacterium acnes biofilms has also been reported using α-dsDNA and atmospheric scanning electron microscopy (47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…The nonisogenic mutant, however, demonstrated elevated levels of fractal structures, which appears to have a role in enabling biofilm nutrient exchange, and feedback mechanisms. Extracellular RNA also plays an important role in the initial steps of biofilm synthesis, though its overall function is less important . Overall, the biofilm synthesized by NTHi has been found to release extracellular DNA and a β ‐glucan …”
Section: Immunologic Evasionmentioning
confidence: 99%
“…Extracellular RNA also plays an important role in the initial steps of biofilm synthesis, though its overall function is less important . Overall, the biofilm synthesized by NTHi has been found to release extracellular DNA and a β ‐glucan …”
Section: Immunologic Evasionmentioning
confidence: 99%